Interfacial spinellisation of MgO–C/Al2O3–C composite functional refractory component at high temperatures. Issue 2 (15th January 2021) - Gu, Qiang; Zhang, Yanxiang; Ma, Weikui; Liu, Guoqi; Liu, Xinhong; Li, Hongxia
Abstract: During the service of MgO–C/Al2 O3 –C composite functional refractory component, MgAl2 O4 (MA) will be formed at the interface between MgO–C materials and Al2 O3 –C materials, thereby, decreasing the bonding strength at the interface and eventually resulting in damage to the material. In this study, the properties of samples consisting of a single material and composite refractory component heat-treated at different temperatures were determined. The effects of interfacial mass transfer on the properties of the composite refractory components were investigated, and the interfacial spinellisation of the MgO–C/Al2 O3 –C composite functional refractory component at high temperatures was studied. Furthermore, we introduced MA into MgO–C or Al2 O3 –C to reduce the interfacial mass transfer. The results show that MA is formed in Al2 O3 –C after heat treatment at 1550 °C because Mg vapor diffuses into the Al2 O3 –C material through the interface and reacts with it. The formation of MA at the interface reduces the bonding strength of the Al2 O3 –C/MgO–C composite functional refractory component. The addition of an interphase (MA) cannot effectively reduce the mass transfer effect.